Human-Wildlife Conflict and its Implication for Conservation at Sundarpur, Udayapur, Eastern Nepal - Pokharel, Manoj; Aryal, Chandramani (International Journal of Environment, 2020)
Local people are the major stakeholders of biodiversity conservation. Human-wildlife conflict (HWC) could result in a negative attitude of the general public towards wildlife adding challenges for conservation. This is more applicable in the landscapes which are outside the protected area (PA) coverage. But, the majority of HWC related studies in Nepal have centered on PAs and their peripheries. This study documents the prevailing situation of HWC in Sundarpur of Udayapur district that shelters some HWC prone wildlife species, while situating outside PA. Data about conflict and people’s perception of wildlife conservation was collected using household surveys supplemented by key informant interviews and direct observation. Monkeys (93%, n=93) and elephants (86%, n=86) were found to be the major animals involved in the conflict, mostly resulting in crop raiding, the major form of conflict as reported by (95%, n=95) of respondents. Livestock depredation cases were mostly by common leopard (84%, n=21) and sloth bear was involved in the majority of human attack cases (90%, n=9). The results showed increasing trend of conflicts for elephants (63%, n=63) and monkeys (73%, n=73), while declining trend for sloth bear (64%, n=64), wild boar (85%, n=85), and leopard (46%, n=46). People believed the natural attraction of wildlife towards crops and livestock to be the major driving factor of conflict. Majority of respondents had a positive attitude towards wildlife conservation. However, implementation of community based conflict management strategies, robust compensation schemes along with conservation education programs are highly essential to achieve desired conservation success.